Integration of chemical and manual control methods for sustainable weed management in inbred and hybrid rice (Journal of the Bangladesh Agricultural University, 2017)
Herbicidal weed control is gaining popularity in the developing countries but its efficacy still remains unclear. Therefore, an experiment was conducted to find out appropriate weed management practices for inbred and hybrid rice. The experiment comprised of inbred and hybrid varieties (two of each), and eight weed control treatments arranged in randomized complete block design with three replicates. Hybrid varieties performed better in terms of yield attributes and yield than inbred varieties. The highest grain yield (5.3 t ha−1) was obtained from the hybrid Agrodhan-12 and the lowest one (4.3 t ha−1) was from inbred Binadhan-7. Weed free treatment resulted in the highest grain yield (6.1 t ha−1) and the lowest one was with weedy treatment (1.96 t ha−1). The highest grain yield was obtained from Agrodhan-12 in weed free condition (6.9 t ha-1), while the lowest value was in inbred BRRI dhan49 under weedy condition (1.73 t ha−1). Weed-free treatment and the treatments of Pretilachlor fb Penoxsolum, Pretilachlor fb hand weeding, and Pendimethalin fb hand weeding showed similar performances in reducing weed density and eventually resulted in similar and the highest grain yield. Based on these results it may conclude that Pretilachlor applied at 2 days after transplanting (DAT) fb Penoxsolum at 21 DAT is the best weed management option. But from sustainability viewpoint, Pretilachlor or Pendimethalin applied at 2 DAT along with one hand weeding at 35 DAT may be recommended for effective weed management in inbred and hybrid rice during monsoon season.J. Bangladesh Agril. Univ. 15(2): 158-166, December 2017